Pengaruh Pengaruh Penuaan Penduduk, Harapan Hidup, dan Pengeluaran Terhadap Pertumbuhan Ekonomi Indonesia - Novriza Putri Cahyanti; Grace Natalia Marpaung (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The increase in the number of elderly people creates various challenges in every aspect of life. The increase in the number of elderly people is also accompanied by a reduction in the birth rate and an increase in life expectancy in Indonesia, causing changes in the population structure. Per capita expenditure is used to see the condition of the economy. This study aims to analyze the effect of population aging, life expectancy and expenditure on economic growth in 34 Indonesian provinces from 2018 to 2023. This research is a quantitative research using panel data regression analysis method. Based on the results of the model specification test, the Fixed Effect Model is the best model used in this study.  The results showed that the population aging variable had a positive but insignificant effect on economic growth in Indonesia. Meanwhile, the life expectancy variable and the per capita expenditure variable have a positive and significant effect on economic growth in Indonesia.